2002
DOI: 10.1179/joc.2002.14.3.285
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Treatment Combinations for Chronic Hepatitis B Infection

Abstract: Chronic hepatitis B virus (HBV) infection is a leading cause of cirrhosis and hepatocellular carcinoma worldwide. Its prevalence approaches 10% in hyper endemic areas. The aim of treating chronic HBV infection is to halt progression of liver injury by suppressing viral replication or eliminating infection. This study was planned to evaluate the advantages of combination therapy with interferon-alpha plus second-generation nucleoside analogues (lamivudine or famciclovir), or vaccination with a pre-S2 and S prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…13 Lamivudine is able to cause normalization of aminotransferase activities at the end of treatment and the suppression of viral load in a high percentage (95.5%) of cases. 5 In groups 2 and 3 in the present study, high percentages of ALT normalization and HBV DNA clearance were seen in comparison with group 1.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…13 Lamivudine is able to cause normalization of aminotransferase activities at the end of treatment and the suppression of viral load in a high percentage (95.5%) of cases. 5 In groups 2 and 3 in the present study, high percentages of ALT normalization and HBV DNA clearance were seen in comparison with group 1.…”
Section: Discussionsupporting
confidence: 48%
“…Lamivudine resistance as a result of mutant/variant viruses is observed in 19% of children after 1 year, a figure that may increase by an average of 20% per year 13 . Lamivudine is able to cause normalization of aminotransferase activities at the end of treatment and the suppression of viral load in a high percentage (95.5%) of cases 5 . In groups 2 and 3 in the present study, high percentages of ALT normalization and HBV DNA clearance were seen in comparison with group 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an attempt to improve immunogenicity, vaccines combining HBsAg with hepatitis B immunoglobulin were tested in untreated individuals, but ultimately this had similarly disappointing results (Supporting information, Table S2, (76)(77)(78)(79)(80)). Even in combination with nucleos(t)ide analogues or interferon treatment, vaccine therapy showed no additional benefit over nucleos(t)ide analogues alone (81)(82)(83)(84)(85)(86)(87). Another recombinant vaccine CVI-HBV-002 delivering the long, medium and small HBV surface proteins (surface/pre-S2/Pre-s1 regions) with adjuvant (L-pampo) is currently in Phase II clinical trials in chronic HBV patients, although results are yet to be reported (88).…”
Section: Recombinant Vaccinesmentioning
confidence: 99%